2015
DOI: 10.1093/cid/civ493
|View full text |Cite
|
Sign up to set email alerts
|

Communication Challenges During the Development and Introduction of a New Meningococcal Vaccine in Africa

Abstract: Background. A new group A meningococcal conjugate vaccine was developed to eliminate deadly meningitis epidemics in sub-Saharan Africa.Methods. From the outset of the project, advocacy and communication strategies were developed and adjusted as the project evolved in Europe, Africa, India, and the United States. Communications efforts were evidence-based, and involved partnerships with the media and various stakeholders including African ministries of health, the World Health Organization, UNICEF, Gavi, the Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 6 publications
(8 reference statements)
1
22
0
Order By: Relevance
“…Yet the rich natural resources which are mostly used to enrich elites leading to corrupt practices and diverting development focus, private sector not independent but part of an elite linked system of rent seeking; hostile attitude of many governments towards the private sector, except where they benefit directly [28,30,34]. Furthermore weak and egocentric leadership problems including lack of democracy and culture of patronage and big men chieftain style of ruling, Africa's low population density, lack of critical mass of skilled people to participate in development and urban bias in development to the neglect of rural areas, land holding structures which discourage entrepreneurship and failure to take responsibility to rebuild their own countries including other bureaucracy and socio-economic bottlenecks and challenges 1,5,9,17,19] Our findings showed that information and knowledge are urgently needs in revamping small business and income generating opportunities, practical information on how to eradicate poverty, self-employment opportunities agricultural knowledge to start agricultural projects [17,20,27]. For vulnerable children including elderly people need more adequate health information and recreational/physical opportunities, financial information 'to know where to get medical insurance loans, skills and know how to manage finances and hygiene information.…”
Section: Evidence-based Poverty Alleviation and Sustainable Pandemic/mentioning
confidence: 83%
See 3 more Smart Citations
“…Yet the rich natural resources which are mostly used to enrich elites leading to corrupt practices and diverting development focus, private sector not independent but part of an elite linked system of rent seeking; hostile attitude of many governments towards the private sector, except where they benefit directly [28,30,34]. Furthermore weak and egocentric leadership problems including lack of democracy and culture of patronage and big men chieftain style of ruling, Africa's low population density, lack of critical mass of skilled people to participate in development and urban bias in development to the neglect of rural areas, land holding structures which discourage entrepreneurship and failure to take responsibility to rebuild their own countries including other bureaucracy and socio-economic bottlenecks and challenges 1,5,9,17,19] Our findings showed that information and knowledge are urgently needs in revamping small business and income generating opportunities, practical information on how to eradicate poverty, self-employment opportunities agricultural knowledge to start agricultural projects [17,20,27]. For vulnerable children including elderly people need more adequate health information and recreational/physical opportunities, financial information 'to know where to get medical insurance loans, skills and know how to manage finances and hygiene information.…”
Section: Evidence-based Poverty Alleviation and Sustainable Pandemic/mentioning
confidence: 83%
“…Eventually, evidence management and sharing process thus became responsible to drive the shared behavioural changes and best practices with an understanding at the same time, important to improve of the overall preparedness, emergency response to care service delivery for impact [17,27].…”
Section: Promoting Evidence-based Translation Into Public Policies Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, this affordable vaccine so-called MACV or MenAfriVac ® was developed by Serum Institute of India and prequalified in 2009 by WHO. MACV is being introduced in the African meningitis belt countries since 2010 to eliminate meningococcal meningitis caused by N. meningitidis A. MACV was introduced firstly in Burkina Faso [3,[11][12][13][14][16][17][18][19][20][21][22]. Only the health districts that are at highest risk were selected to introduce MenAfriVac ® .…”
Section: Introductionmentioning
confidence: 99%